2018
DOI: 10.1002/aur.2020
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic functional connectivity analysis reveals decreased variability of the default‐mode network in developing autistic brain

Abstract: Accumulating neuroimaging evidence suggests that abnormal functional connectivity of the default mode network (DMN) contributes to the social‐cognitive deficits of autism spectrum disorder (ASD). Although most previous studies relied on conventional functional connectivity methods, which assume that connectivity patterns remain constant over time, understanding the temporal dynamics of functional connectivity during rest may provide new insights into the dysfunction of the DMN in ASD. In this work, dynamic fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 81 publications
3
58
0
Order By: Relevance
“…Previous dynamic functional connectivity studies demonstrated that too short window length can increase the risk of introducing artifacts in dynamic functional connectivity analysis and reducing reliability of functional connectivity, and too long window lengths can obscure the temporal variations of dynamic functional connectivity (Preti, Bolton, & Ville, ). Thus 50 TRs was selected as the window length in the current study to balance the specificity and sensitivity for dynamic functional connectivity calculation (He et al, ; Li, Liao, et al, ). To verify the robustness of the sliding‐window analysis, we replicated our findings with different window lengths (30 TRs and 80 TRs) and shifting step (1TR) (Figures S1 and S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous dynamic functional connectivity studies demonstrated that too short window length can increase the risk of introducing artifacts in dynamic functional connectivity analysis and reducing reliability of functional connectivity, and too long window lengths can obscure the temporal variations of dynamic functional connectivity (Preti, Bolton, & Ville, ). Thus 50 TRs was selected as the window length in the current study to balance the specificity and sensitivity for dynamic functional connectivity calculation (He et al, ; Li, Liao, et al, ). To verify the robustness of the sliding‐window analysis, we replicated our findings with different window lengths (30 TRs and 80 TRs) and shifting step (1TR) (Figures S1 and S2, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Capturing the functional connectivity dynamics has been validated to provide new insights into the brain networks of neuropsychiatric disorders, including epilepsy (Li et al, ), depression (Liao et al, ) and schizophrenia (Damaraju et al, ). Investigations of dynamic functional connectivity in ASD have revealed aberrant dynamics of functional connectivity (Chen, Nomi, Uddin, Duan, & Chen, ; Guo et al, ; He et al, ). For example, enhanced temporal variability of intrinsic functional connectivity was observed in individuals with ASD, implying increased intra‐individual variance of brain networks across time (Falahpour et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, rsfMRI data were preprocessed by Data Processing & Analysis for Brain Imaging (DPABI V3.0, http://rfmri.org/) [Yan, Wang, Zuo, & Zang, ], an open‐source package based on Statistical Parametric Mapping (SPM8, https://www.fil.ion.ucl.ac.uk/spm/) and MATLAB (MathWorks). For every subject, the steps of image preprocessing were as follows: (a) the first five volumes were discarded to allow magnetization stabilization; (b) time‐slicing and realignment were performed; (c) functional and structural images were manually reoriented; (d) structural images were co‐registered to functional images and segmented into gray matter, white matter, and cerebrospinal fluid; (e) nuisance covariates were regressed (including Friston 24 head motion parameters [Friston, Williams, Howard, Frackowiak, & Turner, ] and white matter and cerebrospinal fluid signals); (f) functional images were normalized into Montreal Neurological Institute standard space by Diffeomorphic Anatomical Registration Through Exponentiated Lie algebra [Ashburner, ] and resampled to 3.0 × 3.0 × 3.0 mm 3 ; (g) spatial smoothing was performed (Gaussian kernel of 6 mm FWHM); (h) Filtering (0.01–0.08 Hz) was applied to reduce the effects of low‐frequency drifts and high‐frequency aliasing; and (i) image volumes with FD >0.2 mm were scrubbed to reduce the effect of head motion using spline interpolation [He et al, ; Xin et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, DFC has not been widely used to assess ASD, and most investigations paid more attention to clustering results [de Lacy, Doherty, King, Rachakonda, & Calhoun, 2017;Guo et al, 2018;He et al, 2018;Mash et al, 2019;Rashid et al, 2018;Yao et al, 2016] instead of metrics such as the SD Falahpour et al, 2016;He et al, 2018]. In our work, we give more interest in these straightforward characteristics, which could provide more insight into neural mechanisms underlying ASD in terms of temporal variability.…”
Section: Introductionmentioning
confidence: 99%
“…Similar dFC studies in epilepsy revealed state‐specific impairments of functional connectivity patterns in participants with epilepsy compared with healthy controls (Liao, Zhang, et al, ; Liu et al, ). Individuals with ASD were also confirmed to exhibit abnormal temporal variability in functional architecture at rest (Falahpour et al, ; He et al, ; Zhang et al, ). Several studies have examined functional connectivity profiles of the rAI at rest in ASD (Abbott et al, ; Ebisch et al, ; von dem Hagen et al, ).…”
Section: Introductionmentioning
confidence: 99%